(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article covers the theoretical and methodological foundations of training future primary school teachers to methodologically improve the efficiency of learning lessons based on an innovative approach. The study scientifically analyzes the issues of developing methodological competence based on modern pedagogical education paradigms, in particular, the competency-based approach, constructivist education theory, and the ideas of innovative pedagogy. It also substantiates the didactic possibilities of using innovative technologies in organizing learning lessons and their impact on the quality of primary education. The scientific research used theoretical analysis, comparative analysis and generalization methods, and the results show that improving the professional training of future teachers based on an innovative approach serves to increase educational efficiency.